(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
This paper aims to analyze popular participation in social and political conflicts in the period that corresponds to the construction of the new imperial order in Maranhão, from the adhesion to Independence (1823) to the Balaiada revolt (1838-1841), since conservative interpretations tried to minimize the importance of the wars for independence and also the popular participation in these conflicts that marked the first decades of the Brazilian national state.